Earthquake Disaster Education for Early Childhood Through the Earthquake Escape Game - Safira Badzlin; Pramono Pramono; Munaisra Tri Tirtaningsih (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Indonesian children's knowledge of disaster mitigation is still relatively low compared to developed countries. Therefore, an engaging and accessible educational approach is needed, such as through games. This study employed Research & Development (R&D) with the SYNTHESIS method. Data analysis techniques used included qualitative and quantitative analysis. This research resulted in the educational game Earthquake Escape, designed to enhance early childhood understanding of earthquake disaster mitigation.